Structural Nativisation in Malaysian English: Prepositional Verb Idiosyncrasies - Imm, Tan Siew (SARE: Southeast Asian Review of English, 2017)
This paper is an attempt to find out how innovative PrVs such as comrpise of, demand for, discuss about and discuss on have become so deeply ingrained within the linguistic system of written ME. Using a corpus-based approach, this study compares how these PrVs and their corresponsding single-word verbs (SWVs - compromise, demand and discuss - are used in Malaysian English newspapers. It is hypothesised that there are systematic structural differences between the PrVs and their corresponding SWVs which reveal certain aspects of structural nativisation in ME.